A response based decoupling criterion for multiply-supported secondary systems. - Chaudhuri, Samit Ray
It is often infeasible to carry out coupled analyses of multiply supported secondary systems for earthquake excitations. 'Approximate' decoupled analyses are then resorted to, unless the response errors due to those are significantly high. This study proposes a decoupling criterion to identify such cases where these errors are likely to be larger than an acceptable level. The proposed criterion is based on the errors in the primary system response due to decoupling and has been obtained by assuming (i) the input excitation to be an ideal white noise process, (ii) cross modal correlation to be negligible, and (iii) the combined system to be classically damped. It uses the modal properties of the undamped combined system, and therefore, a perturbation approach has been formulated to determine the combined system properties in case of light to moderately heavy secondary systems. A numerical study has been carried out to illustrate the accuracy achieved with the proposed perturbation formulation. The proposed decoupling criterion has been validated with the help of two example primary secondary systems and four example excitation processes.
Keywords: Multiply supported secondary systems; Seismic analysis; Decoupling criterion; Undamped eigenproperties; Perturbation technique